2017
DOI: 10.18540/jcecvl3iss6pp0824-0828
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Do Queijo Minas Artesanal Do Cerrado Mineiro Da Região Do Alto Paranaíba

Abstract: RESUMO: Com objetivo de avaliar as características físico-químicas durante o período de maturação do queijo minas artesanal, foram coletadas amostras de cinco diferentes produtores na região do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
0
1
1
Order By: Relevance
“…Similar pH results to those found in the present study for cheeses from the Campo das Vertentes region were observed by Costa Júnior et al (2014); in the Cerrado region by Oliveira et al (2017); and in the Campo das Vertentes and Serro regions by Machado et al (2004). According to Monteiro and Da Matta (2018), artisanal Minas cheeses are classified as slightly acidic, and thus, the pH values between 4.76 and 5.43 observed in the present study would be in accordance with this classification.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Similar pH results to those found in the present study for cheeses from the Campo das Vertentes region were observed by Costa Júnior et al (2014); in the Cerrado region by Oliveira et al (2017); and in the Campo das Vertentes and Serro regions by Machado et al (2004). According to Monteiro and Da Matta (2018), artisanal Minas cheeses are classified as slightly acidic, and thus, the pH values between 4.76 and 5.43 observed in the present study would be in accordance with this classification.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Costa Júnior et al (2019) reported for cheeses from the Campo das Vertentes region greater fat content (32.45% to 40.27%) than found in the present study for cheese over 60 days of ripening, and this variation was associated with the gradual increase in fat percentages to the loss of moisture and consequent concentration of total solids. The fat percentage of cheeses from the Cerrado region in the present study was higher than those reported by Oliveira et al (2017), and this difference may be related to the higher moisture contents found by these authors, justifying this variation in cheeses from the same region (Figueiredo et al, 2015;Pereira, 2019). Therefore, differences in fat content in cheese can be associated with several factors in the farmer that influence the percentage of milk fat, such as type of feeding and herd breed, stage of lactation and health of the animals.…”
Section: Discussioncontrasting
confidence: 51%
“…Para cinzas, cloreto de sódio e sal na umidade (Tabela 1), não houve diferença (p > 0,05) entre os queijos fabricados com "pingo" e "rala" e nem influência do período de maturação para nenhum dos dois tratamentos (p > 0,05). Oliveira et al (2017), obtiveram em seu estudo com queijos artesanais, uma média de teor de cloretos de 3,75%, sendo que no seu estudo, os valores de cloreto de sódio ficaram acima do valor de 2% (permitido pela legislação) durante todo o período de maturação.…”
Section: Resultsunclassified